Building Harmony Through Pela Bola: Cultural Capital for Religious Conflict Reconciliation in Maluku - Afdhal; Titing, Bernadus Williem (Asosiasi Profesi Pendidik dan Peneliti Sosiologi Indonesia (AP3SI), 2024)
This study examines the role of Pela Bola as cultural capital in efforts to reconcile religious conflicts in Maluku. The main issue discussed is the social conflict that has plagued Maluku and how Pela Bola can be a medium for creating social harmony. Pela is a traditional conflict reconciliation practice in Maluku, and Pela Bola is interpreted as the use of football as a medium for conflict reconciliation and efforts to create sustainable peace. The research method used is qualitative, with data collection techniques through in-depth interviews, observations, and literature studies. The research findings indicate that local identity can be an important capital in building harmony within the community. In Maluku, Pela Bola, as a culture and local identity, serves as both a medium and cultural capital in religious conflict reconciliation. Pela Bola becomes a strong cultural capital to integrate the community and maintain solidarity in interfaith relations. Football is used as an integration arena that creates a cultural identity based on local wisdom, strengthening kinship relations between the Muslim and Christian communities in Maluku. Based on these findings, it is recommended that the government and community organizations should further support and promote Pela Bola as a primary strategy in religious conflict reconciliation. Additionally, this research contributes to providing insights into the effectiveness of local cultural capital in creating peace and social harmony in post-conflict communities.